Sistem Pendukung Keputusan untuk Penilaian Kinerja Pegawai menggunakan Metode AHP dan COPRAS - Cahyono, Adi Tri; Wibisono, Setyawan (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
Employee performance appraisal system is one of the crucial aspects in human resource management so that the right decision support system is needed for effective decision making. In this study, researchers used a hybrid method by combining the AHP (Analytic Hierarchy Process) and COPRAS (Complex Proportional Assessment) methods where AHP was used to determine the priority weights for each assessment criteria. Furthermore, COPRAS provides employee performance ratings based on these weights. The results show that AHP and COPRAS provide consistent and objective assessments. Alternative A1 consistently gets the highest rank with a value of 100 indicating excellent performance. A2 received the lowest rank with a value of 88.801235174, indicating the need for improvement. This research makes a significant contribution to the development of employee performance appraisal systems with AHP and COPRAS.